A Dynamic Model for Ultrasonic – assisted Extraction of Bio-active Compounds from Natural Products - Trung Kien Tran; Lan Huong Phung; Hoai Nga le; Thi Thu Huyen Nguyen; Xuan Son Nghiem; Van Thiem Pham (ASEAN Journal of Chemical Engineering, 2012)
Ultrasonic technique has been applied for extraction processes, especially for separation of bio-active substances from natural organic products because of the short time requirement, energy saving and easy operating. The ultrasonic-assisted extraction (UE) therefore becomes a promising option. However, a major available obstacle was the lack of appropriate models for designing technological process. This paper presents a dynamic model for the UE process, application of separation of bio-active substances from natural products such as Curcumin from rhizome of Curcuma Longa L., Epigallocatechin from green tea leaf of Camellia Sinensis and Rutin from bud of Sophora Japonica. The agreement between data from experiment and calculated ones with the model indicates that, this dynamic model is suitable for prediction of the UE process and for serving as the base for further investigation into scale-up the extraction process.